Growth Performance of Mature Trees Resulted from Intra and Inter-specific Grafting on Robusta Coffee - Rusdi Evizal; Sugiatno Sugiatno; Setyo Dwi Utomo; Hidayat Pujisiswanto; Setyo Widagdo; Fembriarti Erry Prasmatiwi; Aresta Dwi Stiawan (Universitas Muhammadiyah Yogyakarta, 2018)
To improve yield and cup quality, mature coffee tree as rootstock could be grafted with scion of selected genotype. This research aimed to study growth performance of mature trees resulted from intra and inter-specific grafting on Robusta coffee. The research was arranged in Randomized Complete Block Design with 3 replications. There were 12 treatments of entrees/under-stump genotype for coffee grafting including 8 treatments of intraspecific local Robusta/Robusta grafting and 4 treatments of interspecific coffee grafting of Robusta/Liberica and Arabica/Robusta. The results showed that intraspecific grafting of Robusta/Robusta, Robusta/Liberica, and Arabica/Robusta resulted in grafting mortality of 9.8%, 10.9%, and 24.8%, respectively. Until 28 weeks after grafting, branch growth variables were significantly affected by scion/rootstock of Robusta/Robusta, Robusta/Liberica, and Arabica/Robusta grafting. Grafted Arabica/Robusta coffee showed the poor growth performance. In second year of Robusta/Robusta and Robusta/Liberica growth, generative growth of cherry inflorescence per branch and number of cherries per inflorescence were not affected by scion and rootstock genotypes. Leaf and branch growth were very important variables correlating with other variables.